Premature sign off of audit documents by external auditors of small and medium sized audit firms / Khairunnisa Mohd Jais - Mohd Jais, Khairunnisa (2013)
Premature sign off of audit documents is the behaviour of the external auditors towards their audit progress. The emphasis in the research is to provide information regarding premature sign off that occur in the small and medium sized audit firms. Therefore, the research contains chapters on introduction, background of the study, research issue and methodology, results of findings and conclusions as well as recommendation. The aim of this study are (i) to investigate whether the external auditors of small and medium sized audit firms understand that premature sign off of audit documents is not a proper audit practice; (ii) to investigate whether the external auditors of small and medium sized audit firms commonly practice premature sign off of audit documents of their corporate clients; (iii) to identify the causes contributing towards premature sign off of audit documents by the external auditors of small and medium sized audit firms during audit of their corporate clients; (iv) to examine whether the behavior of premature sign off of audit documents by the external auditors of small and medium sized audit firms affect the users of audit report; and (v) to identify the impacts of premature sign off of audit documents by the external auditors of small and medium sized audit firms on users of audit report. This study is based on primary data. The study shows that the external auditors from small and medium sized audit firms have express their responses through interview and questionnaire. The study provides vital information to the external auditors in issue of the premature sign off of audit documents behaviour. As the external auditors from small and medium sized audit firms, this study might help them to review and aware of the premature sign off of audit documents behaviour.